Profil Gerak Dasar Manipulatif Melempar Siswa di Sekolah Menengah Pertama - Desri Desri; Nuryadi Nuryadi; Carsiwan Carsiwan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2023)
This study analyzes throwing in the basic manupulatif movements of junior high school students in the Bandung city environment. The research method used by researchers uses descriptive research methods with a quantitative approach. The sample in this study was 23 class IX students aged 15-16 years. The data collection used in this study was using a research instrument in the form of observation sheets based on a book by David L Gallahue entitled Developmental Physical Education for Today's Children. These students are likelier to do all the fundamental movement skills given in the early and transitional stages. The results obtained from basic manupulatif movements in the form of throwing motion skills are divided into three groups, including the initial stage (10.62%), transitional stage (5.31%), and mature stage (0%). In conclusion, the results of the study obtained an overview of the various kinds of abilities possessed by students in carrying out various basic manupulatif movements with throwing motion skills. Keywords : Basic manupulatif movements, physical activity, and the COVID-19 pandemic